The Effect of Mycotoxin Deoxynivalenol on Haematological and Biochemical Indicators and Histopathological Changes in Rainbow Trout (Oncorhynchus mykiss). (4th March 2014) - Matejova, Iveta; Modra, Helena; Blahova, Jana; Franc, Ales; Fictum, Petr; Sevcikova, Marie; Svobodova, Zdenka
Abstract : Deoxynivalenol (DON), produced by the Fusarium genus, is a major contaminant of cereal grains used in the production of fish feed. The effect of mycotoxin deoxynivalenol on rainbow trout ( Oncorhynchus mykiss ) was studied using a commercial feed with the addition of DON in a dose of 2 mg/kg feed. The fish ( n = 40 ) were exposed to the mycotoxin for 23 days. The trout were divided into two groups, control and experimental groups. Control groups were fed a commercial feed naturally contaminated with a low concentration of DON (225  μ g/kg feed); experimental groups were fed a commercial feed with the addition of DON (1964  μ g/kg feed). Plasma biochemical and haematological indices, biometric parameters, and histopathological changes were assessed at the end of the experiment. The experimental groups showed significantly lower values in MCH ( P < 0.05 ) . In biochemical indices, after 23-day exposure, a significant decrease in glucose, cholesterol ( P < 0.05 ), and ammonia ( P < 0.01 ) was recorded in the experimental group compared to the control group. Our assessment showed no significant changes in biometric parameters. The histopathological examination revealed disorders in the caudal kidney of the exposed fish. The obtained data show the sensitivity of rainbow trout ( O. mykiss ) to deoxynivalenol.